User-controlled identity management: the key to the future of privacy?. (1st December 2008) - Hansen, Marit
The processing of personal data is a prerequisite of today's participation in the information society, which increasingly implies threats to individuals' privacy. Classical Identity Management Systems (IMS) may even intensify those privacy threats. However, comprehensive user-controlled IMS take a different approach, as they implement privacy principles and aim to help users manage their privacy. This text distinguishes the various notions of privacy and identifies linkage control as a key concept that underlies all privacy issues. The described building blocks for user-controlled identity management support privacy in different ways, e.g., by separating contexts, workflows and the related partial identities from each other, by stating and enforcing the privacy policies that also govern linkability or by enhancing transparency to inform the user about the potential linkages. User-controlled IMS are not a panacea for all privacy problems, but they can act as a gateway and guardian for individuals' privacy. Thereby, they have the potential to become a key tool for future privacy concepts.